Microbiological Quality Assessment of Marketed Broiler Meat in Different Markets of Dhaka City (Research in Agriculture Livestock and Fisheries, 2020)
The present research work was undertaken to assess the bacterial quality and to know the prevalence of zoonotic bacteria from broiler meat samples sold in Krishi market, Bihari camp market, Agargaon market, Taltola market and SAU (Sher-e-Bangla Agricultural University) mini bazar, Dhaka, Bangladesh from January to May 2018. After processing of samples primary culture was done in nutrient broth and nutrient agar media then pure culture was obtained from different selective media. Total Viable Count (TVC), Total Coliform Count (TCC) and Total Salmonella Count (TSC) in broiler meat of different broiler markets were determined. Mean of TVC, TCC and TSC for the Krishi market, Agargoan market, Taltola market, Bihari camp market and SAU Mini market were 5.67, 4.32, 2.96 log10 CFU/g, 5.88, 4.64, 3.56 log10 CFU/g, 6.10, 4.68, 3.78 log10 CFU/g, 6.68,4.87, 3.84 log10 CFU/g and 5.84, 4.25, 3.13 log10 CFU/g respectively. The prevalence of Escherichia coli and Salmonella spp. Were 74% and 42% respectively. E. coli isolates were showed sensitive to Ciprofloxacin (91.6%), Gentamycin (87.5%), Azithromycin (66.66%), and Tetracycline (58%) and resistant to Penicillin (79.16%) then Amoxycillin (75%), Streptomycin (75%) and Ampicillin (58.3%). Highest resistant pattern was showed by Tetracycline (58%), Streptomycin (72.72%), Penicillin (72.72%) and Amoxycillin (63.63%). Highest resistant pattern showed by Amoxycillin (71.42%) and Penicillin (71.42%). This study revealed that broiler meat sold at some local markets of Dhaka city were contaminated with multiple species of multidrug resistant bacteria which may risk for human health.Res. Agric., Livest. Fish.7(2): 261-266,  August 2020